Keharmonisan keluarga kristiani dalam perspektif Efesus 5:22–33: sebuah kajian teologis-pastoral - Kompas, Myjon (STIPAS Keuskupan Agung Kupang, 2025)
Family harmony constitutes a fundamental foundation for the life of the Church and society. However, contemporary Christian families are increasingly confronted with social, economic, cultural, and relational challenges that threaten marital unity and stability. In this context, Ephesians 5:22–33 is often interpreted in a normative or literalistic manner, which may generate tension when applied to modern family realities. This article aims to examine the concept of Christian family harmony from a theological-pastoral perspective based on Ephesians 5:22–33 and to reflect on its relevance for contemporary Christian family life. Employing a library research method, this study applies a theological-pastoral approach through biblical text analysis and critical dialogue with theological and pastoral family literature. The findings indicate that Paul’s teaching on the relationship between husband and wife is not intended to legitimize hierarchical or oppressive relations, but rather to call for mutual love, self-giving, and responsibility rooted in the relationship between Christ and the Church. This perspective affirms that Christian family harmony is fostered through the recognition of equal dignity, dialogical communication, and a spirituality of love responsive to contemporary contexts. Therefore, Ephesians 5:22–33 remains a relevant theological-pastoral foundation for nurturing harmonious Christian families amid the challenges of the modern era.